Magneto Metric Resistivitysoundingover Binomially Overburden - Suabsagun Yooyuanyong, Thickness; ., . (International Journal of Engineering and Technology, 2018)
In this paper, inverse problem with the use of optimization technique is proposed. Mathematicalmodel of steady state magnetic field response is formulated. It is accomplished by using analytical method to solve a boundary value problem in the wave number domain and then transforming back to the special domain. One dimensional geometric model of a two layered earth is considered. Magnetic field response is computed numerically to see their behavior against source-receiver spacing. Unfortunately, there are no fluctuation of the curve to show relations between magnetic field response and conductivity parameters or overburden thicknesssignificantly.However, inversion process with the use of conventional conjugate gradient can beapplied to investigate overburden thickness accurately.Â